Epidemiological analysis of bacterial food poisonings in Poland in 2005-2015 - Łukasz Świerszcz; Anna Roszkowska; Maciej Rutkowski; Halina Piecewicz-Szczęsna (Kazimierz Wielki University, 2017)
Background. Bacterial poisoning is still considered as a major problem in polish society. Epidemiological analysis enables an update of the current status of its etiological agent. The acquired knowledge is essential in diagnostics and preventive medicine. Objective. The objective of the research is revealing current epidemiological status concerning food poisoning frequency in Poland in the years 2005-2015. Material and Methods. Research material used for the epidemiological analysis was taken from reports "Choroby zakaźne i zatrucia w Polsce" prepared by National Institute of Hygiene. Results. In 2005 the number of bacterial food poisoning reached 20076, and in 2015 only 9858. In analyzed period of time, the major reason for them was Salmonella. Bacteria such as Staphylococcus aureus, Clostridium botulinum and Clostridium perfringens had significantly lesser involvement in food poisoning. In parallel, there is alarming increase of poisonings induced by Clostridium perfringens. The rest of analyzed infectious agents presented decrease tendency. Poisonings of unknown etiology was placed the second most frequent bacteria-induced food poisoning reason. Conclusions. General trends indicate decrease of number of registered bacteria- induced food poisoning cases in polish society. The level of Sallmonella spp. infections, which lead to particularly life-threatening complications, is alarmingly high. Furthermore, infections induced by Clostridium perfringes are considered to have inauspicious statistics as well. In the light of these considerations, there is certain necessity of rising better hygiene conditions in everyday life, especially during domestic or public food preparation and consumption.